2011
DOI: 10.1017/s175173111000176x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fast-, medium- and slow-growing strains on meat quality of chickens reared under the organic farming method

Abstract: The characteristics of meat quality, chemical and fatty acid composition, from fast-growing (FG) and medium-growing (MG) meat-type and slow-growing (SG) egg-type chickens reared under organic conditions were compared. Three-hundred and sixty 1-day-old male chicks, equally divided into three experimental groups represented by strains (FG: Cobb 700, MG: Naked neck Kabir and SG: Brown Classic Lohman) were housed into three poultry houses with outdoor pasture availability of 10 m 2 /bird located in the same Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
53
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 27 publications
11
53
1
5
Order By: Relevance
“…Resultados semelhantes foram encontrados por Sarsenbek et al (21) e Sirri et al (27) , que, comparando os cortes peito e coxa, observaram um maior teor de umidade em coxas. Com relação ao sexo, os machos apresentaram maiores teores de umidade (Tabela 3).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Resultados semelhantes foram encontrados por Sarsenbek et al (21) e Sirri et al (27) , que, comparando os cortes peito e coxa, observaram um maior teor de umidade em coxas. Com relação ao sexo, os machos apresentaram maiores teores de umidade (Tabela 3).…”
Section: Resultsunclassified
“…Sirri et al (27) , avaliando a linhagem Lohman Brown, de crescimento lento e criada em sistema semiintensivo, encontraram valor inferior para o índice de trombogenicidade (0,59) do peito. Isso pode ser devido principalmente aos menores teores de C16:0 (ácido palmítico) e C18:0 (ácido esteárico), encontrados neste trabalho, que são considerados como trombogênicos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Sirri et al [23] compared fatty acid profiles of breast and thigh meat among fast-(Cobb 700), medium-(Naked neck Kabir), and slow-(Brown Classic Lohman) growing strain chickens slaughtered at the age of 81 d. The SA, ARA and DHA compositions of the slow-growing strain were significantly higher than those of the fast-and mediumgrowing strains, whereas the MA, POA, and oleic acid (OA, C18:1) compositions of the slow-growing line were significantly lower than those of the fast-and medium-growing lines both in breast and thigh Table 5: The primers and target position in chicken fatty acid desaturase 1 and 2 (FADS1 and FADS2) genes for the mismatch amplification mutation assay.…”
Section: Discussionmentioning
confidence: 99%
“…These reports may suggest that there is a significant strain difference in the fatty acid profile of meat; however, we would like to refer to sex differences of samples in these reports. Rikimaru and Takahashi [2] used Hinai-jidori females because almost 100% of the Hinai-jidori chickens sold commercially are females, whereas Sirri et al [23], Jayasena et al [24], and Boschetti et al [25] used males. In fact, Sirri et al [26] reported that the ARA, DPA, and DHA composition of breast and thigh meat of cocks were significantly higher than those of capons at the age of 180 d. To explain the difference between cocks and capons, the authors supposed that D6D activity is affected by testosterone, since Clejan et al [27] found a decrease of ARA and DHA in castrated rats owing to the lack of testosterone and showed that the administration of testosterone to castrated rats could bring the ARA content to normal values.…”
mentioning
confidence: 99%